Analysis of the Effectiveness of the MSIB Program on Academic Performance and Student Readiness for Work in the Era of Cross-Disciplinary Integration - Akbar, Muh.; Majid, Ahmad Fudhail; Arifin, Ibrahim (PT Mattawang Mediatama Solution, 2025)
This study examines the effectiveness of the Certified Internship and Independent Study Program (MSIB) in enhancing student Academic Performance and Work Readiness, focusing specifically on the integration of cross-disciplinary skills. This quantitative study employs survey data from 155 MSIB participants at Makassar State University. Data were analyzed using simple linear regression to assess the influence of MSIB effectiveness on Academic Performance and Work Readiness. The regression results reveal that the MSIB Program positively and significantly influences both Academic Performance (t = 3.515, p=0.001) and Work Readiness (t = 3.284, p = 0.001). These findings suggest that MSIB serves as an effective strategic intervention, equipping students with the competencies required to compete in a job market demanding cross-disciplinary skill integration.